PHƯƠNG PHÁP MÔ PHỎNG SỐ ĐỘNG HỌC CƠ CẤU TRONG GIA CÔNG CHÍNH XÁC BỀ MẶT CHI TIẾT QUANG - Trọng Hùng, Nguyễn; Văn Khang, Nguyễn; Minh Phương, Nguyễn (Vietnam Journal of Science and Technology, 2017)
This  paper  presents  numerical  simulation method  of  the  kinetics  structure  used  in  optical surface  parts  precision  grinding  machine.  From  the  research,  a  numerical  simulation  program system of relative position, velocity and acceleration of the contrivance disk and grinding disc has been  set  up,  as well  as  the  animation  of  these mechanisms  in  the  optical  parts  surface  precise knuckle-lever  grinding  machines  has  been  created.  This  program  system  is  used  to  study  the kinematic  adjustment  programs  in  processing  precise  optical  surface  parts  with  knuckle-lever grinding  machines  and  also  can  be  valuable  for  the  study  of  the  kinematic  knuckle-lever mechanism used in the other mechanical processing machines. The research covers problems that have not been adequately studied in published documents